Childfree dalam Komunikasi Pranikah Perspektif Al-Qur’an Surah An-Nahl Ayat 72 - Yuvelia Indrawan; Akhmad Rifa’i (Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari Banjarmasin, 2023)
Childfree in marriage gives rise to pros and cons in Indonesian society. In developed countries, childfree is considered a common part of married life, but it is different when applied in Indonesia, where the majority of Muslims understand Shafi'i that the purpose of marriage is to increase offspring. However, as time goes by, the concept of childfree is increasingly widespread on several social media, including Instagram, Facebook and YouTube. This problem encourages the novelty of research results on the concept of childfree when the thread of analysis of the interpretation of the Al-Qur'an is drawn. The meaning of the Qur'an surah An-Nahl verse 72 explains that Allah created humans in pairs and in pairs, many children and grandchildren were born. This study focuses on the library research method using the interpretation of An-Nahl verse 72 from pre-modern to modern times. The research results explain that the concept of childfree is not justified in Islam. Preventive action to prevent the concept of childfree by relying on premarital communication management. Premarital communication has an important role in finalizing preparations for marriage.